2023
DOI: 10.1007/s12020-023-03331-9
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels predict outcomes of COVID-19 in patients with both severe and non-severe disease at hospitalization

Abstract: Purpose Low vitamin D in COVID-19 have been related to worse outcomes. However, most of the studies conducted so far were not-controlled and retrospective, including biases potentially influencing this association. We evaluated 25(OH)vitamin D levels of patients with both severe and non-severe disease at hospital-admission, and in a cohort of control subjects. Moreover, we evaluated sACE-2 levels to investigate the mechanisms underlying the association between vitamin D and COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Studies by di Filippo et al showed a strict association of VD levels with blood GLU and BMI in COVID-19 patients on one hand, and that 25-OHD levels at admission strongly predicted the occurrence of worsening outcomes in COVID-19 independently of the disease severity at presentation. [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by di Filippo et al showed a strict association of VD levels with blood GLU and BMI in COVID-19 patients on one hand, and that 25-OHD levels at admission strongly predicted the occurrence of worsening outcomes in COVID-19 independently of the disease severity at presentation. [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies do not allow us to find a cause-and-effect link between vitamin D and dyslipidemia; however, from the consistent results, it would seem, as in many other fields, that vitamin D deficiency represents a risk marker—in this case, a possible marker of cardiovascular risk. Similarly, inconclusive results have been obtained in several studies involving vitamin D treatment for patients with diabetes [ 120 ] or COVID-19 infection [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Prior studies by Luigi et al have shown that insufficient levels of vitamin D may have a detrimental effect on the prognosis of acute COVID-19, as well as on the development of Long-COVID and the long-term immune response to anti-SARS-CoV-2 vaccination. [35][36][37] The current study investigated the association of vitamin D deficiency to the clinical outcome of hospitalized patients at two COVID-19 referral hospitals in Indonesia. We found that compared to insufficient and sufficient, those with deficient vitamin D status had more number of comorbidities (Table 2).…”
Section: Discussionmentioning
confidence: 99%